Services marketing : people, technology, strategy - Lovelock, Christopher H.; Wirtz, Jochen (New Jersey: World Scientific, 2022)
"Services Marketing: People, Technology, Strategy is the ninth edition of the globally leading textbook for Services Marketing by Jochen Wirtz and Christopher Lovelock, extensively updated to feature the latest academic research, industry trends, new technologies such as artificial intelligence and robotics, and new business models including peer-to-peer sharing platforms. This textbook takes on a strong managerial approach presented through a coherent and progressive pedagogical framework rooted in solid academic research. Featuring cases and examples from all over the world, Services Marketing: People, Technology, Strategy is suitable for students who want to gain a wider managerial view of Services Marketing"--
Includes bibliographical references and index.
Keywords: Marketing -- Management; Professions -- Marketing; Service industries -- Marketing; Customer services -- Marketing